Archiving System Toward the Effectiveness of The Motor Vehicle Insurance Claim Process at Asuransi Jasa Indonesia Ltd. of Branch Office in Palembang - Endrianto, Tarmizi (Utan Kayu Publishing, 2022)
The development of science and technology in the world of information technology today makes all existing organizations, including government and private organizations, are required to make various improvements to be able to meet the demands for fast and accurate information. One of the most influential sources of information in organizations is archives. The existence of archives in the organization is a factor that plays an important role and it is also a determinant in the process of carrying out organizational tasks, especially in government organizations and state-owned enterprises that are oriented to providing direct services to the public, where archives are one of the main factors. Measurement of the performance of an organization. To advance the business of an organization, it is necessary to have the right management support. In managing management requires accurate, precise and fast information. One of the most important pieces of information for the world of work is the record of the business activity itself. The recording is in the archive. Archival management in an office is generally a control activity, organizing documents that are classified as important so that they are properly maintained so that they are easy to find again if needed at any time.Â Â Abstrak:Â Perkembangan Ilmu dan teknologi yang sangat pesat dalam dunia teknologi informasi saat ini membuat semua organisasi yang ada tak terkecuali organisasi pemerintah maupun swasta dituntut untuk melakukan berbagai pembenahan untuk dapat memenuhi tuntutan akan informasi yang cepat dan akurat. Salah satu sumber informasi dalam organisasi yang paling berpengaruh keberadaannya adalah arsip. Keberadaan arsip dalam organisasi menjadi salah satu faktor yang sangat berperan penting dan juga merupakan penentu dalam proses pelaksanaan tugas organisasi khususnya dalam organisasi Pemerintah maupun Badan Usaha Milik Negara yang berorientasi pada pemberian layanan langsung kepada masyarakat luas (public), dimana arsip menjadi salah satu faktor utama pengukuran kinerja suatu organisasi. Untuk memajukan usaha suatu organisasi maka dari itu diperlukan dukungan manajemen yang tepat. Untuk mengelola manajemen diperlukan informasi yang teliti, tepat dan cepat. Salah satu informasi yang sangat penting bagi dunia kerja adalah rekaman dari kegiatan bisnis itu sendiri. Rekaman tersebut terdapat dalam arsip. Pengelolaan kearsipan pada sebuah kantor umumnya adalah kegiatan pengendalian, pengorganisasian terhadap dokumen-dokumen yang tergolong penting agar dipelihara dengan baik sehingga mudah ditemukan kembali apabila sewaktu-waktu diperlukan